EFFECT OF DIETARY VITAMIN E ON REPRODUCTIVE PERFORMANCE, EGG QUALITY AND LARVAE OF CLOWNFISH Amphiprion ocellaris (CUVIER, 1830) - Ngoc, Dao Thi Hong; Hue, Nguyen Thi Nguyet; Tram, Dang Tran; Lu, Huynh Duc; Lam, Ho Son; Sang, Huynh Minh; Than, Doan Van; Dang, Do Hai (Vietnam Journal of Marine Science and Technology, 2019)
This study was carried out to determine the effects of vitamin E (a-tocopherol) in five levels (0, 125, 250, 375 and 500 mg vitamin E/kg feed) in broodfish diets on reproductive, egg and larval quality parameters of clownfish (Amphirion ocellaris). Each treatment was repeated in triplicate and the supplemental feeding trial was arranged for 13 months. The result showed that there were no significant differences in re-maturation and spawning periods, spawning frequency, fecundity, egg diameter and larval size of Nemo fish observed between the treatments. However, diets supplemented with vitamin E positively influenced the rate of egg loss, hatching rate of egg and survival rate of the 3 days post hatch. The overall result of this experiment indicated that the optimum vitamin E requirement of clownfish for reproductive performance was 375 mg vitamin E/kg feed.